Stilistika dan Ideologi Hanada Taha Thomure dalam Pidato di TED Talks: ‘Al Lughah Al ‘Arabiyyah, Wathan’ - Khoirin Nikmah (Uktub: Journal of Arabic Studies, 2022)
When it comes to public speaking, one of the keys to success is stylistics. In this case, the ability to play the stylistic aspect has an effect on the process of persuasion for the audience. This research paper is about Dr. Hanada Taha Thomure's TED Talk, "Al Lughah Al'Arabiyah, Wathan," which took place at Zayed University in Dubai. It aims to explain the stylistic strategy and ideology of Hanada Taha Thomure in the speech. This is a descriptive qualitative study. There are three steps used, including data collection, data analysis, and exposure to data analysis research. The listening method is used to collect data, along with recording and note-taking technique. Meanwhile, data analysis is conducted by analysing stylistics and interpreting ideology. The research shows that there are a large number of stylistic variations in Hanada’s speech, such as repetition, kiasmus, epizeukis, epistrofa, asonansi, simile, metaphor, personification, sinestesia, hyperbole, klimaks, rhetoric, and code switching. Then, the nationalist ideology can be seen in every sentence presented by Hanada, either explicitly or implicitly.